Neuroimaging Outcome Correlation of Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Serial analysis of imaging (thallium-201 [201TI) single-photon emission CT and MRI) examinations was correlated with clinical and histological characteristics of brain tumors in 75 patients monitored for 1 day to 3.9 years (mean, 1.39 years) at the Children's Hospital, Harvard Medical School, Boston.